2002
DOI: 10.2117/psysoc.2002.193
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship Between the Motivated Strategies for Learning Questionnaire and the Learning Process Questionnaire

Abstract: The relationship between the scales of the Motivated Strategies for Learning Questionnaire (MSLQ) and Learning Process Questionnaire (LPQ) was examined using an integrated data approach (Skinner, 1977(Skinner, , 1978 that combined features of multiple regression analysis, canonical correlation, and multiple-set factor analysis. Results based on a Hong Kong sample of upper primary and lower secondary students generally agreed with expectations of how the scales in these two instruments would be associated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Hence, the accuracy of correlations between the subscales and test reliability will be improved because the multidimensional Rasch model takes the measurement error into account in the estimation. The research found that there was a high correlation between the subscales of cognitive strategy use and self-regulation in the Chinese setting, which was consistent with the findings of other research (Rao and Sachs 1999;Sachs et al 2002). It seems that Hong Kong students, like other learners in Confucian culture, usually do not make a distinction between discriminating memorization and understanding (Marton et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Hence, the accuracy of correlations between the subscales and test reliability will be improved because the multidimensional Rasch model takes the measurement error into account in the estimation. The research found that there was a high correlation between the subscales of cognitive strategy use and self-regulation in the Chinese setting, which was consistent with the findings of other research (Rao and Sachs 1999;Sachs et al 2002). It seems that Hong Kong students, like other learners in Confucian culture, usually do not make a distinction between discriminating memorization and understanding (Marton et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Other researchers have shown similar internal consistency reliability estimates for the MSLQ with independent samples [4,31]. Beyond English, the MSLQ has been widely translated into other languages including Greek [32], Hebrew [33], Korean [34,35], Norwegian [36], German [37], and Chinese [17,[38][39][40].…”
Section: Motivated Strategies For Learning Questionnaire (Mslq)mentioning
confidence: 78%
“…In 2011, a meta-analysis by Credé and Phillips (2011) identified 67 studies that had used the MSLQ across 19,900 college students. The MSLQ has also been used at the secondary level in different countries, including America (e.g., Liu, 2003), Germany (e.g., Neber & Heller, 2002), Hong Kong (e.g., Sachs, Law, & Chan, 2002), Israel (e.g., Eshel & Kohavi, 2003), Korea (e.g., Bong, 2001) and Turkey (e.g., Andreou, 2004). …”
Section: Introductionmentioning
confidence: 99%